Need analysis of the production based entrepreneurship training model: learning entrepreneurship in higher education - Ganefri, Ganefri; Hidayat, Hendra; Yulastri, Asmar; Ifdil, Ifdil (Indonesian Institute for Counseling, Education, and Therapy & Indonesian Counselor Association, 2020)
The purpose of this study is to describe the needs analysis of production-based entrepreneurship training models in higher education. This is a quantitative and descriptive research with data purposively collected from 110 students that took entrepreneurship courses using questionnaires. The obtained data analyzed using the descriptive statistics method. Furthermore, this research was limited to the definition stage, which is to obtain information on the analysis of production-based entrepreneurship training needs seen from entrepreneurship learning. The results showed that the need for production-based on entrepreneurship training was categorized at a fairly good level, which contained elements of learning and teaching. Needs analysis is an important research activity used to obtain in-depth information as a basis for carrying out subsequent activities.